2021
DOI: 10.1002/cpe.6752
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to ensure the security of the shared medical data using smart contracts: Organ transplantation sample

Abstract: In recent years, the rapid development in information technologies appears in the form of digitalization, all of the processes in the health domain. Among the state‐of‐art, virtual reality, artificial intelligence, and blockchain technologies are among the most mentioned. In addition, the exponential increase in data kept in the electronic environment causes traditional central applications to face new challenges. The most important of these are accountability, transparency, security, cost, and time efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…As can be seen from Table 4, the majority of research that describes their platforms suggests adopting Ethereum (11 out of 17) [19,[57][58][59]61,64,66,67,70,75,76]. In the remaining six studies, three adopted Hyperledger Fabric [56,65,72], one used Monero [69], and two did not specify the platform they used [68,71]. A recently published study [69] suggested a biometric authentication protocol that permits data processing and storage in an encrypted manner when integrated into a blockchain that is based on a cryptocurrency that prioritises privacy.…”
Section: In-house Validated Blockchain Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen from Table 4, the majority of research that describes their platforms suggests adopting Ethereum (11 out of 17) [19,[57][58][59]61,64,66,67,70,75,76]. In the remaining six studies, three adopted Hyperledger Fabric [56,65,72], one used Monero [69], and two did not specify the platform they used [68,71]. A recently published study [69] suggested a biometric authentication protocol that permits data processing and storage in an encrypted manner when integrated into a blockchain that is based on a cryptocurrency that prioritises privacy.…”
Section: In-house Validated Blockchain Solutionmentioning
confidence: 99%
“…As can be seen in Table 4, eight out of ten research studies that discuss blockchain encourage utilising private blockchain [56,58,59,65,67,72,75,76], whilst the other two studies suggest using public blockchain [19,58]. Users have a definite advantage when using a private blockchain because of its improved security, easier authentication, and scalability.…”
Section: In-house Validated Blockchain Solutionmentioning
confidence: 99%
“…The blockchain-based MDSS may be presented in the form of the formal system: Medical Decision Support System/Model/Method 1 2 3 Blockchain-based framework for organ and/or tissue transplantationframework for organ and/or tissue transplantation by using the fabric hyperledger environment [11] + + Private Ethereum blockchain-based end-to-end organ donation and transplantation system, which provides organ donation and transplantation management, guarantees the fairness and efficiency of the organ allocation process and patients' trust enhancing [22] + + Secured-smart blood and organ donation web developed blockchain-based system, which is transparent and only available only by authorized users by Ethereum Smart Contract [23] + + Blockchain-based organ allocation algorithms on the examples of kidney allocation for solving some of the existing issues in the area of organ donation -different organ allocation policies and guidelines in different countries, storing of data from stakeholders and the matching patients in the central point, etc. [24] + + Machine learning-based classification models for predicting the success of intrauterine insemination therapy [25] + The different components of artificial intelligence were used for selection of the embryos with high implantation potential and with proper ploidy status, for prediction of later embryo development, and for increase of pregnancy and live birth rates, i.e.…”
Section: Problem Statementmentioning
confidence: 99%
“…The authors also raise their concern about social division due to immune and unimmune people. The authors proposed a blockchain‐based data‐sharing approach in Reference 22 that offers the blockchain's reliability, integrity, and decentralization properties. The proposed framework was designed based on blockchain technologies for organ/tissue transplantation by using the Hyperledger Fabric environment.…”
Section: Literature Surveymentioning
confidence: 99%